2003
DOI: 10.1542/peds.111.5.e574
|View full text |Cite
|
Sign up to set email alerts
|

Naturopathic Treatment for Ear Pain in Children

Abstract: ABSTRACT.Objective. Otitis media is 1 of the most frequent diseases of early infancy and childhood and 1 of the most common reasons for children to visit a physician. In the past 2 decades, there has been a substantial increase in the diagnosis of otitis media worldwide. In the United States, 93% of all children have had at least 1 episode of acute otitis media (AOM) by 7 years of age. Otalgia is the hallmark of AOM. Most affected children either complain of earache or manifest behavior that the parents interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 24 publications
2
45
0
4
Order By: Relevance
“…In the third trial by Sarrell (Sarrell 2003b), 90 children aged 5 to 18 years with ear pain were enrolled. The diagnosis and exclusion criteria were as outlined above.…”
Section: E S C R I P T I O N O F S T U D I E Smentioning
confidence: 99%
“…In the third trial by Sarrell (Sarrell 2003b), 90 children aged 5 to 18 years with ear pain were enrolled. The diagnosis and exclusion criteria were as outlined above.…”
Section: E S C R I P T I O N O F S T U D I E Smentioning
confidence: 99%
“…The studies were assessed independently by three authors (JD, ACJ and JW) and differences of opinion were resolved by discussion. Only four trials fulfilled the criteria (Hoberman 1997;Sarrell 2001;Sarrell 2003a;Sarrell 2003b), two trials were reported in one paper (Sarrell 2003a;Sarrell 2003b). An unpublished trial (Matz 2001a) was identified through personal communications but was excluded.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Four trials fulfilled the review inclusion criteria; of these, two were found in the same paper (Sarrell 2003a;Sarrell 2003b). One of the trials (Hoberman 1997) evaluated the efficacy of anaesthetic ear drops (antipyrine, benzocaine and glycerine) for treating ear pain in children with acute otitis media.…”
Section: E S C R I P T I O N O F S T U D I E Smentioning
confidence: 99%
See 2 more Smart Citations